Rabi resonance in Cs atoms and its application to microwave magnetic field measurement. (10th January 2018) - Sun, F Y; Hou, D; Bai, Q S; Huang, X H
Abstract: We have recently presented a technique for measuring unknown microwave (MW) fields based on Rabi resonances induced by the interaction of atoms with a phase-modulated MW field. The single-peak feature of the measurement model makes the technique a valuable tool for simple and fast field measurement. Here we demonstrated a detailed investigation of Rabi resonance of Cs atoms inside a vapour cell. For illustration, we used the Rabi resonance-based field detection technique to determine the field strength inside an X-band cavity for applied power in the range of −21 to 20 dBm. The difference between the practical measurement and the simulation was approximately about 3% for an applied power of 20 dBm, and a higher accuracy could be expected for a larger power input.